IMPLEMENTASI POJOK BACA TEMATIK DALAM MENGEKSPLORASI MINAT BACA SISWA KELAS II SEKOLAH DASAR - Hendi Febrianto; Fulusia Nurmawati; Ahmad Teguh Purnawanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of thematic reading corners as classroom literacy spaces, examine their role in fostering the reading interest of second-grade students, and identify the supporting and inhibiting factors affecting their implementation. The study employed a descriptive qualitative approach and was conducted in Grade II at SDN 1 Wulung and SDN 4 Tanggel, Blora Regency. The participants consisted of two second-grade teachers and ten students selected through purposive sampling. Data were collected through observations, in-depth interviews, simple questionnaires, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings showed that thematic reading corners were implemented through the management of theme-based reading materials, attractive reading space arrangements, student involvement in management, regular reading activities, and the use of books as learning resources. The thematic reading corners contributed positively to fostering students’ reading interest through voluntary reading, peer interaction, and enjoyable reading experiences. Supporting factors included teacher commitment, school support, parental involvement, and students’ enthusiasm. The main obstacles were limited book collections and inadequate literacy support at home. These findings indicated that thematic reading corners could serve as classroom literacy ecosystems that supported the development of reading interest among elementary school students.